Weak interlayers in flexible and semi-flexible road pavements: Part 1 - F Netterberg; M de Beer (Journal of the South African Institution of Civil Engineers, 2012)
Weak layers, interlayers, laminations and/or interfaces in the upper structural layers of road pavements are specifically prohibited in most road-building specifications. However, such layers are extremely common and often lead to premature pavement distress. In Part 1 of this two-part set of papers, it is shown that from experience with heavy vehicle simulator (HVS) and dynamic cone penetrometer (DCP) testing, the presence of such layers and/or conditions at any depth in the structural layers of a flexible or semi-flexible pavement is far more deleterious than is commonly appreciated. In Part 2 the effects of these weak layers are further modelled and discussed using various examples based an HVS testing and mechanistic pavement analyses. In particular, a weak upper base course of a cemented pavement under a thin bituminous surfacing may lead to severe surfacing (and upper base) failure within a matter of weeks to months after opening to traffic, not excluding failure even during construction. In this paper (Part 1), the causes of weak layers, interlayers, laminations and/or interfaces, together with simple methods for their detection during construction and analyses of their effects on the structural capacity of flexible and semi-rigid (cemented) road pavements, are briefly discussed.